50.9k views
17 votes
Evaluate the question

Evaluate the question-example-1

1 Answer

5 votes

Answer:

we conclude that:


\frac{2^{-(4)/(3)}}{54^{-(4)/(3)}}=81

Explanation:

Given the expression


\frac{2^{-(4)/(3)}}{54^{-(4)/(3)}}


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)\:=\:x^(a-b)


\frac{2^{-(4)/(3)}}{54^{-(4)/(3)}}=\left((2)/(54)\right)^{-(4)/(3)}


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


=\frac{1}{\left((2)/(54)\right)^{(4)/(3)}}


=\left((1)/(27)\right)^{-(4)/(3)}


\mathrm{Apply\:exponent\:rule}:\quad \left((a)/(b)\right)^c=(a^c)/(b^c)


=\frac{1}{\frac{1^{(4)/(3)}}{27^{(4)/(3)}}}


=\frac{1}{\frac{1^{(4)/(3)}}{81}}
27^{(4)/(3)}=81


\mathrm{Apply\:the\:fraction\:rule}:\quad (1)/((b)/(c))=(c)/(b)


=\frac{81}{1^{(1)/(3)}}


\mathrm{Apply\:rule}\:1^a=1


=(81)/(1)


=81

Therefore, we conclude that:


\frac{2^{-(4)/(3)}}{54^{-(4)/(3)}}=81

User Nebulae
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.